Low-voltage bulk-driven QFG-regulated self-cascode super MOS transistor - Thongleam, Thawatchai; Suadet, Apirak; Kasemsuwan, Varakorn (My University, 2016)
A bulk-driven super MOS transistor (BD-SMT) for low voltage operation is presented. The proposed transistor achieves a high effective transconductance (Gm(eff)), high effective drain impedance (RD(eff)) and low effective source impedance (RS(eff)). BD-SMT is designed based on regulated self-cascode and negative feedback techniques. The transistor been designed using a 0.18 μm CMOS technology and operated from a 0.4 V supply with a static power consumption of 12 μW. The simulation results showed higher Gm(eff), larger RD(eff) and smaller RS(eff) as compared to those of simple bulk-driven MOS transistor.
Keywords: bulk-driven; low voltage; regulated self-cascode